(untitled) (Revista LIDER, 2020)
Remote areas are territories defined by their shortcomings, and are analyzed from their distance, their connectivity problems or their lack of economic dynamism. In Chile, this phenomenon is addressed through integration measures, mainly through public institutions and the market. However, less attention is paid to the definitions made from the territories to characterize the evident differences with poles of development. This article questions the notion of territorial integration of these areas as a means to promote their development and improve their quality of life. In particular, it exposes the omissions and obstacles faced by remote areas when trying to meet goals defined at a distance. Based on semi-structured interviews applied in the communes of Aysén and Cabo de Hornos, in Southern Chile, we identify daily problems of inhabiting extreme territories, including challenging climate, connectivity and economic base. The analysis also reveals local particularities of these communes and their possibilities of acting towards the integration of these areas on their own terms.